Pengaruh Pelayanan dan Kualitas Produk Terhadap Loyalitas Pelanggan - Purba, Jan Horas Veryady; Sulistiono, Sulistiono (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
Service and product quality is an important factor in order that an enterprise keeps running competition. The enterprise has to cultivate good relationship with the customers and keeps striving to increase service and product quality so that the consuners keep having loyalty to the enterprise. To get competitive excellence, every enterprise must be able to satisfy the consummers. Therefore, the strategy based on the management’s commitment to increase service and product quality to satisfy the consumers should be done continually, thereby the consumers’ satisfaction will be created. This research was conducted to find out the effect of service and pruduct quality on the consumers’ loyalty to the enterprise, that is McDonald’s. The method used is interviewing, library study, and field research by questionnaire. The research was carried out at McDonald’s Indonesia located in Jalan Pajajaran Bogor. McDonald’s Indonesia is an enterprise producing food and beverage. The evaluation result on this research shows that the steps done by McDonald’s in maintaining The consumers’ loyalty are providing service and product quality and providing better and more comfortable oulet for the consumers. It should be taken note of as well, that is providing more and more satisfied service and product quality and creating more variation of its products, so that the consumers will be attracted to by them. Thereby, the enterprise has to maintain the consumers to be more loyal to McDonald’s. Keywords:service; product quality; consumers’ loyalty